The Dose Makes the Poison. (8th October 2021) - Brodtmann, Amy; Huq, Aamira
Abstract : Most genes cause disease when the function of at least one copy of the gene is disrupted (e.g., loss-of-function mutations) or compromised (e.g., missense mutations). Gain of function, resulting from increased dose of a gene product, is a less common mechanism of disease causation. Neurologists would be familiar with Charcot-Marie-Tooth disease type 1A caused by duplications of the PMP22 gene. Gene duplications are also well known in neurodegenerative diseases, such as duplications of the amyloid precursor protein gene ( APP ), resulting in early-onset Alzheimer dementia (AD) and cerebral amyloid angiopathy (CAA), and copy number increases of the synuclein-alpha gene, SNCA, causing dementia with Lewy bodies or Parkinson disease dementia.